EVALUATION OF IMMUNOLOGICAL PARAMETERS IN PATIENTS WITH POSTTRAUMATIC OSTEOARTHROSIS TREATED WITH RADON THERAPY - E. Yu. Udartsev (Медицинская иммунология, 2014)
Abstract. The article presents results of immunological evaluation of 74 patients with posttraumatic osteoarthritis of knee joint, and 29 health humans. The data indicate that progression of posttraumatic inflammatory changes in joint cavity is accompanied by signs of systemic inflammation and disorders in cytokine balance. Following treatment including radon therapy, a significant trend for normalization of all the studied immunological data was observed in majority of patients. The findings provide further evidence for application of radon therapy, in order to treat patients with posttraumatic inflammatory changes of the joint cavity.